A perceptual study of Ozisa FM We the people program on the Unknown Gunmen issue in Owerri municipal - Azubuike, Chieme; Uche Dorathy, Isaac (COMMICAST, 2024)
The risk associated with insecurity is alarming as such people need to be security conscious in order to stay safe. The aim of the study was to investigate the public perception of Ozisa FM We the people programme on the Unknown gunmen issue in Owerri municipal council. The study was framed around the agenda setting theory. The study adopted a survey research approach with the use of questionnaire as the instrument for data collection. The population is 171,102, of which 384 were derived using Survey Monkey's online sample size calculator. The non-proportionate quota sampling and purposive sampling approaches were used. The data was analysed using simple percentages. Results revealed that 47.4% of the respondents confirmed that they are exposed to Ozisa FM's We the People Programme on the issue of the Unknown Gunmen to a moderate extent. Findings also showed that 55.0% of the respondents had the perception that the We the people programme has been effective in joining hands with the authority to curtail the Unknown Gunmen's activities. It was concluded that audience are moderately exposed to the Ozisa FM We the people programme. Despite their level of exposure to the programme they still perceive it in a positive light, due to its role in helping curtail the menace of the Unknown gunmen in Owerri, Imo State. It was recommended that they need to sustain their efforts in joining hands with the appropriate stakeholders with the goal of ending the issue of the Unknown gunmen, especially in Imo State.